2006
DOI: 10.1001/jama.295.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of β-Blockers, Amiodarone Plus β-Blockers, or Sotalol for Prevention of Shocks From Implantable Cardioverter Defibrillators<SUBTITLE>The OPTIC Study: A Randomized Trial</SUBTITLE>

Abstract: Despite use of advanced ICD technology and treatment with a beta-blocker, shocks occur commonly in the first year after ICD implant. Amiodarone plus beta-blocker is effective for preventing these shocks and is more effective than sotalol but has an increased risk of drug-related adverse effects.Clinical Trials Registration ClinicalTrials.gov Identifier: NCT00257959.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
408
5
26

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 711 publications
(445 citation statements)
references
References 13 publications
6
408
5
26
Order By: Relevance
“…However, the OPTIC study demonstrated the additional benefit of amiodarone in combination with beta‐blockers for preventing future ICD interventions in those with inducible or spontaneous ventricular tachyarrhythmias 32. Nonetheless, previous reports were frequently confounded by a nonuniform patient population 33, 34.…”
Section: Management Of Vt In Nicmmentioning
confidence: 99%
“…However, the OPTIC study demonstrated the additional benefit of amiodarone in combination with beta‐blockers for preventing future ICD interventions in those with inducible or spontaneous ventricular tachyarrhythmias 32. Nonetheless, previous reports were frequently confounded by a nonuniform patient population 33, 34.…”
Section: Management Of Vt In Nicmmentioning
confidence: 99%
“…Antiarrhythmic drugs are the usual long-term treatment strategy, and in most patients amiodarone is chosen in the first line. Although amiodarone or sotalol may reduce ventricular tachyarrhythmias, they are often ineffective or may not be tolerated [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Decreasing the number of shocks triggered by the defi brillator is an important treatment goal for a variety of reasons. A high burden of shocks can contribute to mortality by causing myocardial necrosis and promoting or exacerbating ventricular dysfunction (40), (41) .…”
Section: Antiarrhythmic Drugsmentioning
confidence: 99%
“…ICDs treat VTs by delivering shocks or by providing antitachycardia pacing, effectively preventing arrhythmic sudden death. Nevertheless, the ICD-delivered shocks are painful and can substantially decrease the quality of life (40), (61) , a characteristic that calls attention to the importance of therapies that prevent VT recurrence. Because of the toxicity of antiarrhythmic drugs and their failure in preventing recurrences, ablation (surgical or catheter-based) is, for many patients, the only option to treat recurrent VT.…”
Section: Ablation Therapymentioning
confidence: 99%